Analisis Variasi Ketebalan Kepala pada pemeriksaan Mastoid Proyeksi Axiolateral Metode Schuller terhadap Gambaran Anatomis - Dartini Dartini; Galuh Negrawati; Bagus Dwi Handoko (Poltekkes Kemenkes Semarang, 2016)
Background: Axiolateral projection of mastoid examination with Schuller method using angle range of 25°-30° caudad according to Bontrager (2010). The difference thickness of the human’s head will cause range of angles of axiolateral projection of mastoid examination using Schuller projection. The inappropriate angle will affect the different anatomical information. Axiolateral projection of mastoid examination using Schuller projection in Radiology Installation of dr. Soetomo Hospital used an angle that is 25° for all patients with different thickness of the head. This study aims to determine the differences in anatomical image clarity on radiographic image of axiolateral projection of mastoid examination using Schuller method with an angle that is 25° with variations of head thickness between 12 to 14.5 cm.Methods: This research was a quantitative research with an experimental approach. Subjects of this reearch were 10 respondents. Data analyzed statistically by Kruskal Wallis test and Mann Whitney test.Results: The results showed that there was difference in anatomical image of axiolateral projection of mastoid examination with Schuller method with 25° angle. Result of statistical test to get optimal radiographic image of mastoid using Schuller method showed the significant value, which was 0,000. Differences in anatomical image was also shown on the assessment results from 10 respondents which most of respondents assess anatomical features on a 14.5 cm head thickness was very good.Conclusion: There were differences anotomical information of mastoid radiograph using schuller method with thickness variaton of head. Head thickness of 14.5 cm can show anatomical image of the mastoid air cells, bony labirinth, condyle mandible, temporomandibular joint (TMJ), Aacousticus the external meatus (MAE) and tegmen tympani. The CR angle should be considered based on head thickness.